HANDOUT PEMBELAJARAN BIOLOGI SMP BERBASIS RISET MORFOLOGI AKAR TUMBUHAN DI LAHAN GAMBUT PASCA KEBAKARAN - Zainun, Zainun; Syafii, Wan; Fauziah, Yuslim; L.N. Firdaus, L.N. Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Peatland fires undermine ecosystems altogether, including vegetation. But many plants can regrowth after the fire. This research is aimed to produce Biology Handout of Junior High School by utilizing the result of a study on the morphological characteristics of plant roots that survived in post-fire peatlands. For this purpose, a survey study was conducted in Rimba Panjang Village, Kampar District, Riau Province in February-October 2017. Quadratic method and purposive sampling technique were applied at gradient of fire incident 2009, 2013, 2014, 2015, 2016 and 2017. The parameters observed were morphology of plant root of dominant sapling level (main root and lateral root). Data were analyzed descriptively-qualitative. The results of the observation were 6 dominant species of Sapling that were able to regrowrth after the fire, ie Evodia roxburghiana, Acacia mangium, Ilex cymosa, Eugenia pelyta, Macaranga triloba and Cratoxylon arborescens. Among the six species, the Cratoxylon arborescens and Acacia mangium were the species that have fairly good root morphological characteristics with deep root systems and considerable amounts of lateral roots. It can be concluded that deep root system with a sufficient number of lateral roots is a root morphological characteristic of the dominant plant sapling level following peat fires in Rimba Panjang. These characteristics can be utilized for the development of learning handout of Biology Science of SMP class VII on Environmental Pollution (KD 3.8) and Structure and Function of Grade VIII (KD 3.4). Testing the useful of handouts produced and the benefits of enriching student learning materials in a classical setting is highly recommended. Keywords : Biology learning, junior high school, handout, peatland, post fire, root morphology